The evaluation of teaching performance through questionnaires at the university: Its legitimacy according to the literature and the requirements for it to be effective - Zamora Serrano, Evelyn (2021)
Although it is true that the evaluation of teaching performance through questionnaires applied to the student population is a practice that has been widely institutionalized in universities, it is questioned mainly by those who do not share its theoretical and methodological support or by those who have not developed a evaluation culture. To establish its legitimacy, this essay presents a journey through the literature that discusses the justification for teacher evaluation. This journey ranges from understanding the concept of teaching, to the relationship between teacher evaluation and improvement in the quality of teacher performance. The purpose of the essay is to discuss the usefulness of the questionnaire as a teacher evaluation mechanism and the requirements to guarantee its effectiveness. It is concluded that the results of a higher education institution are related to the quality of its teaching population and that the questionnaire is one of the strategies that have been used the most to evaluate the teaching staff. Its use has become widespread as it allows focusing on the evaluation of teaching; however, its effectiveness depends on the fulfillment of a series of conditions that entail consciously redirecting the teaching work. It also follows that, to strengthen the teacher evaluation process, other techniques must be applied that complement it and contribute to the enrichment of the culture of academic evaluation.